Titanium Nanotube Modified With Silver Cross-Linked Basic Fibroblast Growth Factor Improves Osteoblastic Activities of Dental Pulp Stem Cells and Antibacterial Effect - Albashari, Abdullkhaleg Ali; He, Yan; Albaadani, Mohammed A.; Xiang, Yangfan; Ali, Jihea; Hu, Fengting; Zhang, Yuan; Zhang, Keke; Luo, Lihua; Wang, Jianming; Ye, Qingsong (Frontiers in Cell and Developmental Biology, 2021)
Titanium modifications with different silver loading methods demonstrate excellent antibacterial properties. Yet pure silver nanoparticles with limited bioactive properties may delay regeneration of bone surrounding the dental implant. Therefore, loading silver with bioactive drugs on titanium surfaces seems to be a very promising strategy. Herein, we designed a silver (Ag) step-by-step cross-linking with the basic fibroblast growth factor (bFGF) by polydopamine (PDA) and heparin on titanium nanotube (TNT) as its cargo (TNT/PDA/Ag/bFGF) to improve the implant surface. Our results showed that TNT/PDA/Ag/bFGF significantly enhanced the osteogenic differentiation of dental pulp stem cells (DPSCs). It also showed an excellent effect in bacterial inhibition and a reduction of pro-inflammatory factors through inhibition of M1 macrophage activity. These results showed that bFGF cross-linked silver coating on TNTs presented good osteogenic differentiation and early anti-infiammatory and antibacterial properties. Together, this novel design on titanium provides a promising therapeutic for dental implants.